Clinical significance of suboptimal hormonal levels in men with prostate cancer treated with LHRH agonists - Kawakami, Jun; Morales, Alvaro (Canadian Urological Association Journal, 2013)
Purpose: We examined the serum levels of testosterone (T) (total and bioavailable) dehydroepiandrosterone (DHEA), follicle stimulating (FSH), luteinizing (LH), and prostate specific antigen (PSA) in men receiving treatment with luteinizing hormone releasing-hormone (LHRH) agonists for metastatic prostate cancer, to determine the efficacy of these agents in lowering T levels and whether a possible relationship exists between PSA values, as a surrogate measure of tumor activity, and hormone levels. Materials and Methods: This was a single center prospective study of patients on LHRH agonists. Of all 100 eligible patients, 31 did not qualify: 10 were receiving their first injection, 13 were on intermittent hormonal therapy, 7 refused to enter the trial, and 1 patient’s blood sample was lost. Therefore, 69 patients were included in the final analysis. Each patient had their blood sample drawn immediately before the administration of a LHRH agonist. The new proposed criteria of <20ng/dL (0.69 nmol/L) of total testosterone was used to define optimal levels of the hormone in this population. Results: Of the 69 patients, 41 were on goserelin injections, 21 on leuprolide, and 7 on buserelin. There was no statistical difference in hormone levels between any of the medications. Overall, 21% of patients failed to reach optimal levels of total testosterone. PSA levels were higher in this group. There was a statistically significant correlation between PSA and testosterone levels as well as between PSA and FSH. Serum levels of PSA however, did not correlate with those of bio-available testosterone. Conclusions: Failure to reach optimal levels of testosterone occurs in patients on LHRH agonist therapy. Higher PSA values are more commonly found in patients with sub-optimal levels of testosterone receiving LHRH analogs but the clinical importance of this finding has not been established. There is no significant difference with respect to hormonal levels reached among patients on a variety of LHRH agonists. Total testosterone determinations should be considered in patients on LHRH agonist therapy, particularly when the PSA values begin to rise since it may lead to further beneficial hormonal manipulation.